Preparation method of waterproof and breathable layer and electrode of metal fuel cell
Patent Information
- Application Number
- CN202611302458.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-09-25
AI Technical Summary
[0005]本发明要解决的技术问题是提供一种金属燃料电池防水透气层及电极的制备方法,能够解决现有技术中存在的易干裂、无法连续成膜、一致性差、效率低、PTFE乳液用量大、成本高的技术难题,推动金属燃料电池的产业化发展
[0016]本发明的优点在于:通过干粉预混+低温烘烤+干湿混合+挤压+压延的连续化制备流程,向低温烘烤后的干粉中添加特定比例有机溶剂润湿粉体,体系不会像传统湿法一样形成浆料,由此实现防水透气层连续化制备;有效解决单一干法制备过程中易干裂、无法成膜的问题,提升产品一致性,且兼顾防水透气性能与导电性能,能够有效阻止电解质渗透、保障氧气扩散,同时高效传导电子,提升金属燃料电池的整体稳定性和使用寿命,适用于各类金属燃料电池防水透气层的规模化制备,满足金属燃料电池规模化生产的需求;同时有机溶剂可回收再利用,降低成本、提升环保性;
Smart Images

Figure CN122822776A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal fuel cell fabrication technology, specifically to a method for fabricating a waterproof and breathable layer and electrodes for a metal fuel cell. Background Technology
[0002] The waterproof and breathable layer is one of the core functional layers of a metal fuel cell, serving as both a catalyst composite carrier and a conductive layer. It plays a crucial role in the operation of the battery: on the one hand, it needs to have excellent waterproof performance to prevent electrolyte solution penetration and avoid catalytic activity decay; on the other hand, it needs to have good breathability to ensure that oxygen diffuses smoothly to the catalytic reaction site, while also undertaking electron conduction to ensure the efficient conduction of electrochemical reactions. Its performance directly affects the power density, cycle life, and operational stability of the metal fuel cell.
[0003] Currently, traditional manufacturing processes for waterproof and breathable layers in metal fuel cells have several drawbacks, making it difficult to meet the demands of large-scale production: First, traditional processes often use PTFE emulsion and carbon materials in a 1:1 ratio, with at least three times the volume of ethanol added as an organic solution for mixing. The large amounts of PTFE emulsion and ethanol result in high manufacturing costs, and the emulsion drying process is prone to uneven pore size and shrinkage deformation, affecting the consistency of the waterproof and breathable layer's performance. Second, existing processes typically use an open-milling method to prepare the waterproof and breathable layer. This method cannot achieve continuous film formation and requires batch-by-batch preparation, which... The first problem is that the production process is inefficient, time-consuming, and labor-intensive, and the thickness, density, and performance of individual batches of products vary greatly, resulting in poor consistency and making it difficult to adapt to the mass production of large-scale metal fuel cells. The second problem is that some processes attempt to prepare waterproof and breathable layers using dry methods, selecting acetylene black, graphite, and PTFE powder as raw materials. After steps such as premixing, low-temperature baking, and open milling and rolling, the acetylene black has a large specific surface area and high surface activity. During multiple open milling and rolling fiberization processes, the powder surface is prone to "oil sheen," dry cracking, and caking, making it impossible to form a continuous and dense film. Therefore, the pure dry preparation scheme is difficult to industrialize.
[0004] In response to the shortcomings of the aforementioned traditional processes, the industry urgently needs a low-cost, continuous production process for preparing waterproof and breathable layers that can simultaneously ensure stable waterproof and breathable properties as well as conductivity. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide a method for preparing a waterproof and breathable layer and electrode for a metal fuel cell, which can solve the technical problems existing in the prior art, such as easy cracking, inability to form a continuous film, poor consistency, low efficiency, large amount of PTFE emulsion, and high cost, and promote the industrialization of metal fuel cells.
[0006] To solve the above-mentioned technical problems, the technical solution of the present invention is: a method for preparing a waterproof and breathable layer for a metal fuel cell, characterized in that: a dry-wet mixing improvement method is adopted, combining the steps of preforming, extrusion, calendering, compounding and curing, to achieve continuous production of the waterproof and breathable layer, specifically including the following steps: S1. Raw material preparation: Select acetylene black, graphite, and PTFE powder as raw materials, or select acetylene black and PTFE powder as raw materials, and mix the selected powders. S2. Dry powder premixing and low-temperature baking: Premix three materials, acetylene black, graphite and PTFE powder or two materials, acetylene black and PTFE powder, in a high-speed mixer to obtain a preliminary mixed dry powder; Place the preliminary mixed dry powder in a sealed container and bake it in a low-temperature oven to soften the PTFE powder and remove residual moisture from the powder to obtain the mixed dry powder. S3. Wetting and mixing: Add 10% by volume of organic solvent to the baked mixed dry powder to obtain wetted powder. The organic solvent is one or more of isododecane, isohexadecane, and white oil. The mixture is stirred at high speed to allow acetylene black and graphite to fully absorb the organic solvent, making the powder wet. During the high-speed shearing and stirring process, the PTFE powder is stretched into fibrous form and forms encapsulated agglomerated particles with acetylene black and graphite. S4. Blanking and Extrusion Molding: The wetted powder is placed in a blanking machine and extruded to form a dense blank; the blank is placed in an extruder with a three-stage heating zone, and the blank is softened by gradient heating and extruded into a continuous sheet film, which is then wound up. S5. Continuous calendering and thinning: The wound sheet film is placed into a continuous calender for continuous calendering and thinning to obtain a waterproof and breathable semi-finished product of a set thickness. S6. Organic solvent recovery and baking: The waterproof and breathable layer semi-finished product is baked to remove residual organic solvents and recover the volatilized organic solvents to obtain the waterproof and breathable layer.
[0007] Further, in step S1, the mass ratio of acetylene black, graphite, and PTFE powder is 50~90:1~20:10~50; or the mass ratio of acetylene black and PTFE powder is 50~90:10~50; and the raw material powders are all dry powders with a moisture content of ≤0.5%.
[0008] Furthermore, in step S2, the premixing speed is 800~1200 r / min, the high-speed premixing time is 10~15 min, the low-temperature baking temperature is 50~60℃, and the baking time is 2~4 h.
[0009] Furthermore, in step S3, the high-speed stirring speed is 2000~2800 r / min, and the high-speed stirring time is 20~30 minutes.
[0010] Furthermore, in step S4, the extrusion pressure is 5~10MPa to ensure that the blank is free of looseness and pores. The extruder is a four-column extruder with a flat extrusion nozzle at the front end. The flat extrusion nozzle design can ensure that the width and thickness of the extruded film are uniform. The width of the extrusion nozzle is 5~10cm and the thickness is 2~5mm. The temperatures of the three heating zones are set to 80℃ for the extrusion barrel, 100℃ for the middle section, and 110℃ for the outlet section, respectively. The extrusion speed is 3~5cm / s.
[0011] Furthermore, in step S5, the calendering speed is 5~10mm / s, and the calendering thickness is reduced to 0.4~1mm to ensure that the membrane does not break or wrinkle during the calendering process, ensuring that the membrane thickness is uniform and the structure is dense. It can take into account waterproof and breathable performance, electrical conductivity and mechanical strength. The calendering accuracy can reach ±2μm, which is consistent with the accuracy requirements of existing multi-stage roll forming and thinning technology, and is suitable for the use needs of most metal fuel cells.
[0012] Furthermore, in step S6, the temperature for baking the waterproof and breathable layer semi-finished product is 80~150℃, and the baking time is 1~2 hours.
[0013] A method for preparing a metal fuel cell electrode using a waterproof and breathable layer prepared by a metal fuel cell waterproof and breathable layer preparation method is characterized by the following steps: composite treatment: rolling and bonding the waterproof and breathable layer roll material with the catalyst layer roll material, and then rolling and bonding the composite waterproof and breathable layer-catalyst layer composite with the current collector for a second time, so as to realize the integrated composite of the current collector, the waterproof and breathable layer and the catalyst layer, and obtain an integrated electrode. Curing and molding: The composite integrated electrode is cured at high temperature and then naturally cooled to room temperature to obtain a finished metal fuel cell electrode with a waterproof and breathable layer. This curing process can effectively improve the interfacial contact characteristics of each layer, reduce interfacial impedance, eliminate microscopic defects in the membrane, and improve catalyst utilization.
[0014] Furthermore, in the composite processing step, the temperature of the two roll-pressing composites is controlled at 220℃, the roll-pressing pressure is 1~5MPa, and the composite speed is 2~3m / min. This ensures that the waterproof and breathable layer and the catalyst layer are tightly bonded without delamination or gaps. The temperature of the rollers is precisely controlled within ≤±3℃ to ensure the uniformity of the composite interface and avoid problems such as local overheating or poor adhesion. At the same time, it avoids excessive roll pressing that could damage the porous structure of the membrane and ensures breathability.
[0015] Furthermore, in the curing and molding step, the high-temperature curing temperature is controlled at 300℃, and baking is carried out for 30-60 minutes until complete curing, so that the layers are fully fused and completely cured, enhancing the bonding force of the composite interface, improving the structural stability and mechanical strength of the electrode, and avoiding problems such as delamination and peeling during use; the current density of the battery electrode in the magnesium-air battery is ≥80mA / cm. 2 .
[0016] The advantages of this invention are as follows: Through a continuous preparation process of dry powder premixing + low-temperature baking + wet-dry mixing + extrusion + calendering, a specific proportion of organic solvent is added to the low-temperature baked dry powder to wet the powder. Unlike traditional wet processes, this avoids the formation of a slurry, thus enabling continuous preparation of the waterproof and breathable layer. This effectively solves the problems of easy cracking and inability to form a film during single dry preparation, improving product consistency while balancing waterproof and breathable properties with electrical conductivity. It effectively prevents electrolyte penetration, ensures oxygen diffusion, and efficiently conducts electrons, improving the overall stability and lifespan of metal fuel cells. It is suitable for the large-scale preparation of waterproof and breathable layers for various metal fuel cells, meeting the needs of large-scale metal fuel cell production. Furthermore, the organic solvent can be recycled and reused, reducing costs and improving environmental friendliness. Using PTFE powder instead of PTFE emulsion significantly reduces preparation costs while avoiding problems such as uneven pore size and shrinkage deformation during emulsion drying, as well as the potential for surfactants in the emulsion to hinder electron conduction, thus improving the performance consistency of the waterproof and breathable layer. The synergistic process of gradient temperature-controlled extrusion combined with precision calendering avoids material degradation and extrusion distortion caused by sudden temperature changes, increases the compaction density of the membrane, and ensures that the macroscopic thickness and microscopic pore structure of the waterproof and breathable layer are highly uniform. By employing high-temperature roll forming and high-temperature curing molding processes, the current collector, waterproof and breathable layer, and catalyst layer are integrated, eliminating interlayer voids, microscopic defects, and residual stress within the membrane. The resulting electrode exhibits stronger interlayer bonding, making it less prone to delamination and detachment during battery assembly and operation. Simultaneously, it significantly improves interlayer contact resistance, enhancing the overall output performance and lifespan of the metal fuel cell. The entire process is simple and easy to operate, with low equipment investment costs, controllable process parameters, and high repeatability. The finished product thickness can be adjusted as needed, adapting to various metal fuel cells and possessing significant potential for widespread application. Attached Figure Description
[0017] Figure 1 This is a flowchart of the process steps of the present invention; Figure 2 The gradient discharge curves are shown for the metal fuel cell electrodes prepared in Examples 4 and 5 and Comparative Example 1 of the present invention. Figure 3The graphs show the gradient current density curves of three sets of samples prepared according to the embodiments and comparative examples of the present invention. Detailed Implementation
[0018] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. The following embodiments will enable those skilled in the art to more fully understand this invention, but do not limit the invention to the scope of the described embodiments.
[0019] This specific implementation method adopts the following technical solution: (e.g.) Figure 1 As shown, a method for preparing a waterproof and breathable layer for a metal fuel cell employs a modified dry-wet mixing method, combining steps of preforming, extrusion, calendering, lamination, and curing to achieve continuous production of the waterproof and breathable layer. Specifically, the method includes the following steps: S1. Raw material preparation: Select acetylene black, graphite, and PTFE powder as raw materials, or select acetylene black and PTFE powder as raw materials, and mix the selected powders; the mass ratio of acetylene black, graphite, and PTFE powder is 50~90:1~20:10~50; or the mass ratio of acetylene black and PTFE powder is 50~90:10~50; the raw material powders are all dry powders with a moisture content of ≤0.5% to prevent moisture from affecting the powder adsorption performance and molding quality.
[0020] Acetylene black and graphite form a composite conductive framework, creating an efficient electronic conduction pathway to ensure conductivity. At the same time, the porous structure optimizes oxygen diffusion and improves breathability. PTFE powder acts as a waterproof binder, replacing the traditional high-cost, high-volume PTFE emulsion, which significantly reduces production costs while giving the membrane waterproof capabilities and structural strength.
[0021] S2. Dry powder premixing and low-temperature baking: Premix acetylene black, graphite, and PTFE powder, or acetylene black and PTFE powder, in a high-speed mixer at a speed of 800-1200 r / min for 10-15 min to ensure uniform dispersion of the three powders and obtain a preliminary mixed dry powder. Place the preliminary mixed dry powder in a sealed container and bake it in a low-temperature oven at 50-60℃ for 2-4 hours to slightly soften the PTFE, improving its bonding force with acetylene black and graphite. This also removes residual moisture from the powder to prevent pores from forming during subsequent film formation, ultimately obtaining a uniformly mixed dry powder.
[0022] S3. Wetting and Mixing: Add 10% by volume of organic solvent to the baked mixed dry powder to obtain wetted powder. The organic solvent is one or more of isododecane, isohexadecane, and white oil. Stir at high speed for 2000-2800 r / min for 20-30 minutes to allow graphite and acetylene black to fully absorb the organic solvent and the powder to become wetted. Under high-speed shearing, PTFE powder is stretched into fibrous filaments, which wrap acetylene black and graphite to form agglomerated particles, thus solving the defects of carbon powder being easy to dry and crack and difficult to form a continuous film when prepared by pure dry method.
[0023] S4. Preform Forming and Extrusion Molding: The wetted powder is placed in a preform forming machine for extrusion forming at a pressure of 5-10 MPa. After pressing, the preform is free of looseness and internal pores, with uniform thickness and dense structure. The preform is then placed in a four-column extruder with a three-stage heating zone. The front end of the four-column extruder has a flat extrusion nozzle, which ensures uniform width and thickness of the extruded film. The nozzle width is 5-10 cm and the thickness is 2-5 mm. The temperatures of the three heating zones are set to 80°C for the extrusion barrel, 100°C for the middle section, and 110°C for the outlet section. The extrusion speed is 3-5 cm / s. Gradual heating softens the preform, facilitating smooth extrusion while preventing degradation or deformation of the preform due to high temperatures. A continuous sheet film is extruded, continuously wound up, and transferred to the next process, achieving continuous forming of a waterproof and breathable layer and solving the defect of traditional open milling methods that cannot form a continuous film.
[0024] S5. Continuous calendering and thinning: The wound sheet membrane is placed into a continuous calender for continuous calendering and thinning. The calendering speed is 5~10mm / s, and the membrane is calendered to a thickness of 0.4~1mm. The roll gap of the calender is gradually adjusted according to the actual use requirements to obtain a semi-finished waterproof and breathable layer of a set thickness. This ensures that the membrane does not break or wrinkle during the calendering process, guarantees uniform membrane thickness and dense structure, and the calendering accuracy can reach ±2μm. The thickness of the finished product is precisely controlled to meet the use requirements of different types of metal fuel cells.
[0025] S6. Organic solvent recovery and baking: The semi-finished waterproof and breathable layer is baked at a temperature of 80~150℃ for 1~2 hours to remove residual organic solvents from the membrane. The organic solvents volatilized during the baking process are recovered and reused using the principle of distillation and condensation, which can achieve a solvent recovery rate of more than 85% to obtain the finished waterproof and breathable layer.
[0026] A method for preparing a metal fuel cell electrode using a waterproof and breathable layer fabrication method for metal fuel cells includes the following steps: Composite processing: Rolling composite of the waterproof and breathable layer roll and the catalyst layer roll, followed by a second rolling composite of the composite waterproof and breathable layer-catalyst layer with a current collector to achieve integrated composite of the current collector, waterproof and breathable layer, and catalyst layer, resulting in an integrated electrode; The temperature of the two rolling composites is controlled at 220℃, the rolling pressure is 1~5MPa, and the composite speed is 2~3m / min to ensure a tight bond between the waterproof and breathable layer and the catalyst layer, without delamination or gaps. The temperature of the rollers is precisely controlled within ≤±3℃ to ensure the uniformity of the composite interface and avoid local overheating or poor adhesion. At the same time, excessive rolling is avoided to prevent damage to the porous structure of the membrane and to ensure breathability.
[0027] Curing and molding: The composite integrated electrode is subjected to high-temperature curing treatment at 300℃ for 30~60 minutes until fully cured. After natural cooling to room temperature, a finished metal fuel cell electrode with a waterproof and breathable layer is obtained. This curing process can effectively improve the interfacial contact characteristics of each layer, reduce interfacial impedance, eliminate microscopic defects in the membrane, and improve catalyst utilization.
[0028] Example 1: A process for preparing a waterproof and breathable layer for a metal fuel cell, specifically including the following steps: S1: Raw material preparation and pretreatment: Acetylene black and PTFE powder are selected as raw materials and mixed at a mass ratio of 80:20 to obtain electrode powder; the powder moisture content is ≤0.5%.
[0029] S2: Dry powder premixing and low-temperature baking: Add acetylene black and PTFE powder to a high-speed mixer and premix at 1000 r / min for 10 min to obtain a preliminary mixed dry powder; put the preliminary mixed dry powder into a sealed container and bake in a 60℃ low-temperature oven for 2 h to remove trace moisture and make the PTFE powder slightly soft.
[0030] S3: Wetting and Mixing: Add 10% by volume of isododecane to the baked mixed dry powder, place it in a high-speed mixer, and stir at 2800 r / min for 30 minutes to allow acetylene black to fully adsorb the organic solvent, making the powder wet. During the high-speed shearing and stirring process, the PTFE powder is stretched into fibrous form and forms encapsulated agglomerates with acetylene black.
[0031] S4: Preform making and extrusion molding: The wetted powder is placed into the preform making machine and extruded with a pressure of 5MPa to form a dense preform; the preform is placed into a four-column extruder with a flat extrusion nozzle width of 5cm and a thickness of 3mm. The temperatures of the three heating zones are set to 80℃ for the extrusion barrel, 100℃ for the middle section, and 110℃ for the outlet section. The extruder is started to extrude the preform into a continuous sheet film, which is then continuously wound up.
[0032] S5: Continuous calendering and thinning: The wound sheet film is placed into a continuous calender and calendered at a speed of 5 mm / s. The roll gap is adjusted to reduce the film thickness to 0.5 mm.
[0033] S6: Organic solvent recovery and baking: The calendered film is placed in an oven and baked at 120°C for 1 hour to remove residual organic solvents; the volatilized isododecane is recovered and reused through the recovery device at the top of the oven, with a recovery efficiency of 85%.
[0034] Tests have shown that this waterproof and breathable layer has excellent waterproof performance, can be repeatedly folded at 175 degrees without breaking, has good consistency in continuous film formation, and its production cost is reduced by more than 30% compared with traditional processes.
[0035] Example 2: The other steps of Example 2 are the same as those of Example 1, except that in step S1, acetylene black, graphite and PTFE powder are selected as raw materials and mixed in a mass ratio of 70:10:20 to obtain electrode powder.
[0036] In step 2, graphite, acetylene black, and PTFE powder are added to a high-speed mixer and premixed at 1000 r / min for 10 min to obtain a preliminary mixed dry powder; the preliminary mixed dry powder is placed in a sealed container and baked in a 60℃ low-temperature oven for 2 h. In step 3, add 10% by volume of isohexadecane to the baked mixed dry powder, place it in a high-speed mixer, and stir at 2800 r / min for 30 minutes. In step 4, the wetted powder is placed into a blanking machine and extruded under a pressure of 10MPa to form a dense blank; the width of the flat extrusion nozzle of the extruder is 5cm and the thickness is 3mm. In step 5, the wound sheet film is placed into a continuous calender and calendered at a speed of 5 mm / s to reduce the thickness. The roll gap is adjusted to reduce the film thickness to 0.5 mm. In step 6, the calendered film is placed in an oven inside an organic solvent collection box and baked at 120°C for 2 hours to remove residual organic solvents. The volatilized isohexadecane is recovered and reused through a recovery device at the top of the oven, with a recovery efficiency of 90%.
[0037] Tests have shown that this waterproof and breathable layer has excellent waterproof performance, can be repeatedly folded at 175 degrees without breaking, has good consistency in continuous film formation, and its preparation cost is reduced by more than 35% compared with traditional processes. It also has a tight composite interface with the catalyst layer and current collector, with no delamination.
[0038] Example 3: The other steps of Example 3 are the same as those of Example 1, except that in step 1, acetylene black, graphite and PTFE powder are selected as raw materials and mixed in a mass ratio of 60:20:20 to obtain electrode powder. In step 2, the mixture is premixed at 1200 r / min for 10 min to obtain a preliminary mixed dry powder; the preliminary mixed dry powder is placed in a sealed container and baked in a 60℃ low-temperature oven for 4 h. In step 3, add 10% by volume of white oil to the baked mixed dry powder, put it in a high-speed mixer, and mix at 2800 r / min for 30 minutes. In step 4, the wetted powder is placed into a blanking machine and extruded under a pressure of 8MPa to form a dense blank; the width of the flat extrusion nozzle of the extruder is 5cm and the thickness is 4mm. In step 5, the wound sheet film is placed into a continuous calender and calendered at a speed of 10 mm / s to reduce the thickness. The roll gap is adjusted to reduce the film thickness to 0.5 mm. In step 6, the calendered film is placed in an oven and baked at 150°C for 2 hours to remove residual organic solvents; the volatile white oil is recovered and reused through the recovery device at the top of the oven, with a recovery efficiency of 92%.
[0039] Tests have shown that this waterproof and breathable layer has excellent waterproof performance, can withstand repeated 175-degree folding without breakage, exhibits good consistency in continuous film formation, reduces manufacturing costs by more than 32% compared to traditional processes, and has high mechanical strength, making it suitable for the use of high-power metal fuel cells.
[0040] Example 4: A method for preparing a metal fuel cell electrode, comprising the following steps: Composite treatment: The waterproof and breathable layer roll material and the catalyst layer roll material obtained in Example 1 are placed into a composite machine, and the composite temperature is controlled at 220°C and the rolling pressure is 5MPa for rolling composite; then the composite part and the current collector are placed into the composite machine and composited again using the same parameters.
[0041] Curing and molding: Place the composite electrode in a 300℃ oven and bake for 30 minutes to fully cure it; let it cool naturally to room temperature to obtain the finished metal fuel cell electrode with a waterproof and breathable layer.
[0042] Example 5: A method for preparing a metal fuel cell electrode, comprising the following steps: Composite treatment: The waterproof and breathable layer roll material and the catalyst layer roll material obtained in Example 2 are placed into a composite machine, and the composite temperature is controlled at 220°C and the rolling pressure is 5MPa for roll pressing composite; then the composite part and the current collector are placed into the composite machine and composited again using the same parameters.
[0043] Curing and molding: Place the composite electrode in a 300℃ oven and bake for 30 minutes to fully cure it; let it cool naturally to room temperature to obtain the finished metal fuel cell electrode with a waterproof and breathable layer.
[0044] Comparative Example 1: This comparative example uses the traditional PTFE emulsion open milling method to prepare a waterproof and breathable layer, with PTFE accounting for 50% by mass. The prepared waterproof and breathable layer, along with the catalyst layer and current collector, is used to prepare a metal fuel cell electrode.
[0045] The waterproof and breathable layer in Comparative Example 1 was slightly broken after repeated 175-degree folding, making it impossible to form a continuous film and resulting in high preparation costs.
[0046] The waterproof and breathable layers prepared in Examples 1-3 of this invention have a preparation cost that is more than 30% lower than that of traditional processes. They can achieve continuous film formation and have significantly better mechanical strength than the comparative examples. This shows that the preparation process of this invention effectively solves the defects of traditional processes and achieves low-cost, continuous, and high-performance preparation of waterproof and breathable layers, which can meet the needs of large-scale production of metal fuel cells.
[0047] The metal fuel cell electrodes prepared in Examples 4-5 and the metal fuel cell electrode prepared in Comparative Example 1 were subjected to discharge tests.
[0048] The test conditions are as follows: magnesium alloy is used as the negative electrode, neutral saturated saline solution is used as the electrolyte, the distance between the positive and negative electrodes is 3 mm, and the reaction area of the catalyst layer is 10 cm². 2 A gradient discharge test was performed. The gradient discharge curve results of the gradient discharge test are as follows: Figure 2 As shown.
[0049] Test results: Example 4 uses the waterproof and breathable layer prepared in Example 1, and Example 5 uses the waterproof and breathable layer prepared in Example 2. The catalyst layer is the same. Example 1 uses only acetylene black as the conductive phase, while Example 2 combines acetylene black and graphite. The PTFE addition amount is the same in both. Figure 2 As can be seen, there is no significant difference in discharge performance between Examples 4 and 5 within the low current density range. However, at current densities greater than 80 mA / cm²... 2 Differences were observed, and the polarization attenuation of the electrode prepared by adding a graphite waterproof and breathable layer in Example 2 was significantly better than that of the electrode prepared by adding a waterproof and breathable layer in Example 1.
[0050] like Figure 2 As shown, Comparative Example 1 uses a traditional open-milling process, with the PTFE content of the waterproof and breathable layer reaching as high as 50%, resulting in poor membrane breathability and high internal resistance. In contrast, the membranes used in Examples 4 and 5 contain only 20% PTFE, significantly improving conductivity and breathability, and resulting in higher battery discharge voltage. This demonstrates that the higher the PTFE content, the greater the electrode internal resistance and the worse the breathability.
[0051] The waterproof and breathable layer and matching electrodes prepared by the process of this invention have a comprehensive performance improvement of more than 50% compared with the traditional process in Comparative Example 1.
[0052] The electrodes prepared in Examples 4 and 5, and Comparative Example 1, were subjected to current density tests in a neutral saline magnesium-air battery. The gradient current density curves are shown below. Figure 3 As shown, by Figure 3 It can be seen that the batteries prepared with the waterproof and breathable layers in Examples 1 and 2 have better feasibility and output performance than the batteries prepared with the waterproof and breathable layer in Comparative Example 1.
[0053] The foregoing has shown and described the basic principles and main features of the present invention, as well as its advantages. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a waterproof and breathable layer for a metal fuel cell, characterized in that: A dry-wet hybrid method is adopted, combining steps such as preforming, extrusion, calendering, lamination, and curing to achieve continuous production of waterproof and breathable layers. Specifically, the following steps are included: S1. Raw material preparation: Select acetylene black, graphite, and PTFE powder as raw materials, or select acetylene black and PTFE powder as raw materials, and mix the selected powders. S2. Dry powder premixing and low-temperature baking: Premix three materials, acetylene black, graphite and PTFE powder or two materials, acetylene black and PTFE powder, in a high-speed mixer to obtain a preliminary mixed dry powder; Place the preliminary mixed dry powder in a sealed container and bake it in a low-temperature oven to soften the PTFE powder and remove residual moisture from the powder to obtain the mixed dry powder. S3. Wetting and mixing: Add 10% by volume of organic solvent to the baked mixed dry powder to obtain wetted powder. The organic solvent is one or more of isododecane, isohexadecane, and white oil. The mixture is stirred at high speed to allow acetylene black and graphite to fully absorb the organic solvent, making the powder wet. During the high-speed shearing and stirring process, the PTFE powder is stretched into fibrous form and forms encapsulated agglomerated particles with acetylene black and graphite. S4. Blanking and Extrusion Molding: The wetted powder is placed in a blanking machine and extruded to form a dense blank; the blank is placed in an extruder with a three-stage heating zone, and the blank is softened by gradient heating and extruded into a continuous sheet film, which is then wound up. S5. Continuous calendering and thinning: The wound sheet film is placed into a continuous calender for continuous calendering and thinning to obtain a waterproof and breathable semi-finished product of a set thickness. S6. Organic solvent recovery and baking: The waterproof and breathable layer semi-finished product is baked to remove residual organic solvents and recover the volatilized organic solvents to obtain the waterproof and breathable layer.
2. The method for preparing a waterproof and breathable layer for a metal fuel cell according to claim 1, characterized in that: In step S1, the mass ratio of acetylene black, graphite, and PTFE powder is 50~90:1~20:10~50; or the mass ratio of acetylene black and PTFE powder is 50~90:10~50; and all raw material powders are dry powders with a moisture content of ≤0.5%.
3. The method for preparing a waterproof and breathable layer for a metal fuel cell according to claim 1, characterized in that: In step S2, the premixing speed is 800~1200 r / min, the high-speed premixing time is 10~15 min, the low-temperature baking temperature is 50~60℃, and the baking time is 2~4 h.
4. The method for preparing a waterproof and breathable layer for a metal fuel cell according to claim 1, characterized in that: In step S3, the high-speed stirring speed is 2000~2800 r / min, and the high-speed stirring time is 20~30 minutes.
5. The method for preparing a waterproof and breathable layer for a metal fuel cell according to claim 1, characterized in that: In step S4, the extrusion pressure is 5~10MPa, the extruder is a four-column extruder, the front end of the four-column extruder is provided with a flat extrusion port, the width of the extrusion port is 5~10cm, the thickness is 2~5mm, the temperature of the three heating zones is set to 80℃ for the extrusion barrel, 100℃ for the middle section and 110℃ for the outlet section, and the extrusion speed is 3~5cm / s.
6. The method for preparing a waterproof and breathable layer for a metal fuel cell according to claim 1, characterized in that: In step S5, the rolling speed is 5~10mm / s, the rolling thickness is reduced to 0.4~1mm, and the rolling accuracy reaches ±2μm.
7. The method for preparing a waterproof and breathable layer for a metal fuel cell according to claim 1, characterized in that: In step S6, the temperature for baking the waterproof and breathable layer semi-finished product is 80~150℃, and the baking time is 1~2 hours.
8. A method for preparing a metal fuel cell electrode using a waterproof and breathable layer prepared according to any one of claims 1 to 7, characterized in that: The process includes the following steps: Composite processing: The waterproof and breathable layer roll material and the catalyst layer roll material are rolled together by rolling, and then the composite waterproof and breathable layer-catalyst layer composite is rolled together with the current collector for a second time to achieve the integrated composite of the current collector, waterproof and breathable layer and catalyst layer, and obtain an integrated electrode. Curing and molding: The composite integrated electrode is cured at high temperature and then naturally cooled to room temperature to obtain a finished metal fuel cell electrode with a waterproof and breathable layer.
9. A method for preparing a metal fuel cell electrode according to claim 8, characterized in that: In the composite processing step, the temperature of the two roller pressing composites is controlled at 220℃, the roller pressing pressure is 1~5MPa, the temperature accuracy of the rollers is controlled within ≤±3℃, and the composite speed is 2~3m / min.
10. A method for preparing a metal fuel cell electrode according to claim 8, characterized in that: In the curing and molding step, the high-temperature curing temperature is controlled at 300℃, and baking is performed for 30~60 minutes until complete curing; the current density of the battery electrode in the magnesium-air battery is ≥80mA / cm². 2 .